Ferdinand II of Aragon (1479–1516) - Marta Serrano-Coll (Encyclopedia, 2021)
Ferdinand II king of Aragon (1479–1516). He was the fourth king of the Trastámara dynasty, which had first come to power after the Compromise of Caspe, reached after Martin I died with no living descendants in 1410. Although in terms of artistic patronage Ferdinand II was not as active as his wife Elisabeth I, he was still aware that the wise use of artistic commissions in reinforcing ideas and concepts favourable to the institution of the monarchy. He is a highly important figure in the history of Spain because, along with Elisabeth, he was one of the Catholic Monarchs and thus represents a new conception of power based on their joint governance, a fact that is reflected in the iconography found in his artistic commissions across all genres. All of the images are evidence of how King Ferdinand, at the end of the Middle Ages, wanted to be recognised by his subjects, who also used his image for legitimising and propagandistic purposes. Nobody else in the history of the Hispanic kingdoms had their image represented so many times and on such diverse occasions as did the Catholic Monarchs.